COMPARATIVE CHARACTERISTICS OF PRODUCTIVE EMPLOYMENT AND EMPLOYMENT COMPOSITION IN THE INTERNATIONAL LABOR MARKET (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article shows ways to apply the recommendations of the International Labor Organization to increase fruitful and productive employment in the country. Its calculation and analysis based on indicators of the national labor market is one of the important tasks in the fight against poverty in many countries. The current poverty in the global labor market highlights the need to calculate productive employment if there is a working population among those affected. The article describes in detail the indicators of productive employment, their analysis and the method of its calculation. Also at the end of the article, recommendations are aimed at increasing productive employment.
Keywords: globalization, global labor market, productive employment, working poverty, deficit of productive employment.